High Central Venous Pressure and Right Ventricle Size Are Related to Non-decreased Left Ventricle Stroke Volume After Negative Fluid Balance in Critically Ill Patients: A Single Prospective Observational Study - Hua, Zhao; Xin, Ding; Xiaoting, Wang; Dawei, Liu (Frontiers in Medicine, 2021)
Background: Optimal adjustment of cardiac preload is essential for improving left ventricle stroke volume (LVSV) and tissue perfusion. Changes in LVSV caused by central venous pressure (CVP) are the most important concerns in the treatment of critically ill patients. Objectives: This study aimed to clarify the changes in LVSV after negative fluid balance in patients with elevated CVP, and to elucidate the relationship between the parameters of right ventricle （RV）filling state and LVSV changes. Methods: This prospective cohort study included patients with high central venous pressure (CVP) (≥8 mmHg) within 24 hours of ICU admission in the Critical Medicine Department of Peking Union Medical College Hospital. Patients were classified into two groups based on the LVSV changes after negative fluid balance. The cutoff value was 10% The hemodynamic and echo parameters of the two groups were recorded at baseline and after negative fluid balance. Results: A total of 71 patients included in this study. 40 in VI Group (LVOT VTI increased ≥10% )and 31 in VNI Group (LVOT VTI increased <10%). Of all patients, 56.3% showed increased LVSV after negative fluid balance. In terms of hemodynamic parameters at T0, patients in VI Group had a higher CVP（p<0.001）and P(v-a)CO2 (p<0.001) and lower ScV02 (p<0.001) relative to VNI Group ,Regarding the echo parameters at T0, the RVD/LVD ratio(p<0.001), DIVC end-expiratory (p<0.001), and ∆LVOT VTI(p<0.001) were higher, while T0 LVOT VTI(p<0.001) was lower, in VI Group patients. The multifactor logistic regression analysis suggested that a high CVP and RVD/LVD ratio ≥0.6 were significant associated with LVSV increase after negative fluid balance in critically patients. The AUC of CVP was 0.894. A CVP> 10.5 mmHg provided a sensitivity of 87.5% and a specificity of 77.4%. The AUC of CVP combined with the RVD/LVD ratio≥0.6 was 0.926, which provided a sensitivity of 92.6% and a specificity of 80.4%. Conclusion： High CVP and RVD/LVD ratio ≥0.6 were significant associated with RV stressed in critically patients. Negative fluid balance will not always lead to a decrease, even an increase, in LVSV in these patients.